Expert Evaluation of Pharmacovigilance System Documents Included in the Registration Dossier - I. I. Snegireva; E. O. Zhuravleva; N. Yu. Velts (Безопасность и риск фармакотерапии)
The Russian Federation and the member states of the Eurasian Economic Union (EAEU) are working on the creation of a common pharmaceutical market. EAEU marketing authorisation may be granted to those pharmaceutical companies whose activities comply with the Good Pharmacovigilance Practice (GVP). The aim of the study was to analyse pharmacovigilance system documents submitted as part of registration dossiers of medicines and to identify problems that may arise during preparation of the pharmacovigilance system master file (PSMF). The authors analysed the PSMF, which makes part of the registration dossier, for compliance with the EAEU GVP requirements for submission, content, and completeness of all sections of the document. They identified the most common types of errors in PSMF preparation and analysed conditions when a PSMF is required or, alternatively, when a brief summary of the pharmacovigilance system of the marketing authorisation holder will suffice. The paper summarises specific aspects of incorporating pharmacovigilance system documents in regulatory submissions, as well as aspects of presenting pharmacovigilance system data when bringing the registration dossier in line with the EAEU requirements. This information may be useful for marketing authorisation holders who are the main stakeholders in the medicine authorisation process and who are directly involved in the pharmacovigilance system management during the authorisation and post-authorisation stages of the drug life-cycle.